2016
DOI: 10.1007/s13142-016-0433-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrating knowledge across domains to advance the science of health behavior: overcoming challenges and facilitating success

Abstract: Health behaviors often co-occur and have common determinants at multiple levels (e.g., individual, relational, environmental). Nevertheless, research programs often examine single health behaviors without a systematic attempt to integrate knowledge across behaviors. This paper highlights the significant potential of cross-cutting behavioral research to advance our understanding of the mechanisms and causal factors that shape health behaviors. It also offers suggestions for how researchers could develop more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The factors affecting hospice decision and decision are also important. In the traditional knowledge–attitude–practice model, knowledge influences an individual's health attitude, and then both have effects on behaviour or practice (Klein et al, ). In accordance with this model, our findings showed that the impact of knowledge of hospice care on attitude towards hospice care was the most robust, followed by attitude towards hospice care on decision towards hospice care and knowledge of hospice care on decision towards hospice care (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The factors affecting hospice decision and decision are also important. In the traditional knowledge–attitude–practice model, knowledge influences an individual's health attitude, and then both have effects on behaviour or practice (Klein et al, ). In accordance with this model, our findings showed that the impact of knowledge of hospice care on attitude towards hospice care was the most robust, followed by attitude towards hospice care on decision towards hospice care and knowledge of hospice care on decision towards hospice care (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…This recognition has transformed what previously had been specializations by developmental scholars in particular problem behaviors, e.g., delinquency, or drinking behavior, or tobacco use, or precocious sexual activity, etc., into greater acceptance of the obligation in developmental research to engage the larger pattern of involvements across those previously segmented domains. [For a similar issue in health behavior research, the report of a recent meeting sponsored by the National Cancer Institute (Klein et al 2016) stated: "… research programs often examine single health behaviors without a systematic attempt to integrate knowledge across behaviors." (p. 1); and concluded that "Integrating knowledge across behavioral domains is a public health imperative."…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…The sample size was relatively small but was adequate for structural equation model construction, which confirmed that all models tested in the study were acceptably fitted to the data. The applied retrospective data collection followed standardized protocols, and different behaviors were investigated at the same time as suggested in a recent article [24]. Second, the study specifically focused on the complex relationships between adolescent's health behavior and knowledge.…”
Section: Limitationsmentioning
confidence: 99%